254 Collision Tumor of Endometrial Neuroendocrine Carcinoma and Low-Grade Endometrial Stromal Sarcoma: Case Report and Review of Literature. (11th January 2018) - Rivera-Colon, Glorimar; Niu, Shuang; Peng, Yan
Abstract: Introduction: Neuroendocrine carcinoma (NEC) of the endometrium is an uncommon histologic subtype of endometrial cancer (0.8%). These tumors are highly aggressive with a propensity for metastasis and poor prognosis. They are often combined with other epithelial carcinomas. We report a case of collision tumor with pure endometrial NEC and low-grade endometrial stromal sarcoma (LGESS). Methods: The patient is a 48-year-old woman who presented with a large abdominal mass for several years. An intraoperative consultation diagnosis of the mass revealed a spindle cell neoplasm. She underwent total hysterectomy, bilateral salpingo-oophorectomy and tumor debulking. Results: Microscopic evaluation demonstrated a LGESS with extensive osseous metaplasia penetrated through myometrium and invaded into pelvic/abdominal cavity, forming a 40 cm mass. This diagnosis is supported by diffuse positivity of CD10 and negativity of caldesmon, desmin, cyclin D1, PAX8, and cytokeratins (CKs) in the tumor cells. Incidentally, small foci of highly atypical cells were noted within the endometrium; the cells show enlarged, round, and hyperchromatic nuclei with "salt and pepper" chromatin. They are diffusely positive for CKs, synaptophysin, chromogranin, PAX8, and Ki67, and negative for TTF1, cyclin D1, ER, and PR. Based on the morphology and immunoprofile, a second diagnosis of endometrial NEC, large cell variant was established. The NEC focally invaded myometrium with involvement of endocervix and extensive lymph-vascular invasion. The tumor metastasized to bilateral ovaries. Subsequently, the patient was treated with cisplatin/etoposide chemotherapy and has been doing well. Postoperative imaging studies of abdomen and chest showed no evidence of metastatic disease. Cytogenetic analysis performed on the LGESS showed abnormal female karyotype (45, XX) with multiple structural and numerical abnormalities. Conclusion: This case demonstrates two histologically and immunophenotypically distinct tumor types (endometrial NEC and LGESS) synchronously present in the endometrium, which is extremely rare. To our knowledge, this collision tumor is the first case reported.